(untitled) (Studia Prawnicze / The Legal Studies, 2009)
Każdy system prawny wymaga stworzenia norm, które zagwarantują jego wykonywanie. W przeciwnym razie mielibyśmy do czynienia jedynie z zasadami moralnymi a nie prawnymi. Z tego względu zagadnienie międzynarodowej odpowiedzialności państwa, jako jedynego pierwotnego podmiotu prawa międzynarodowego, stało się kluczowym przedmiotem kodyfikacji w kwestii określenia zasad tejże odpowiedzialności. Sama analiza odpowiedzialności państwa nie jest zadaniem łatwym, gdyż zdefiniowanie go atrybutami właściwymi dla prawa międzynarodowego niewiele wyjaśnia Konwencja z Montevideo o prawach i obowiązkach państw w art. 1 określa państwo jako „osobę prawa międzynarodowego”, używając czterech atrybutów: (a) stała ludność; (b) określone terytorium; (c) rząd; oraz (d) zdolnośćdo wchodzenia w stosunki z innymi państwami. Ale czym tak naprawdę jest państwo ponoszące odpowiedzialność prawno-międzynarodową? Wydaje się, że najtrafniejszą byłaby odpowiedź, że to twór abstrakcyjny, działający poprzez swych przedstawicieli. W wyroku Trybunału Norymberskiego stwierdzono, że to „nie twory abstrakcyjne dokonały zbrodni, ale zwykli ludzie itylko oni mogą za nie ponieść odpowiedzialność”. This article is devoted to the state’s responsibility for breaches of humanitarian law on the basis of draft articles of future convention on the responsibility of states for internationally wrongful acts. It analyses a development of main concepts, first codifications, achievements of the League of Nations and works in the United Nations Organization. Much attention is paid on the role of the International Committee of the Red Cross in the process of an establishment of the state’s responsibility. Humanitarian law belongs to those branches of international law which are very often violated in present international relations. International character of the state’s responsibility is based on the art. 3 of the fourth Hague Convention of 1907 and art. 91 of the first Additional Protocol of 1977. The source of the responsibility is an act of the state’s organ which constitutes an internationally wrongful act, including serious violations of international humanitarian law enumerated by the Geneva Conventions of 1949. A special group of acts constitutes declicts against cultural property. International character of the responsibility is provided by the treaty law, confirmed by practice as customary rules of humanitarian law and general principles of that system. Responsibility of the state has been provided under certain conditions enumerated in Draft articles. Author describes also sources of the responsibility of states which are: violations and serious violations of humanitarian law. Than conditions excluding responsibility and prohibition to absolve of any liability in respect of breaches. State’s responsibility can be enforced in such forms as: reparations, restitution or satisfaction. International law established a lot of situations in which countermeasures have been excluded. Procedural aspects of the enforcement can be associated with the International Fact Finding Commission, arbitration or by the jurisdiction of national courts. In all those aspects responsibility of the state needs recognition as a consequence of the principle of sovereignty. International law as a system provides parallel responsibility of the state and an individual for the same violations of humanitarian law. Increasing number of international and non-international armed conflicts, became the reason of establishing international criminal tribunals. Their task is to bring natural persons responsible for violations of international humanitarian law to justice. Very similar rules applied to breaches and violations of humanitarian law establish not only responsibility of the state which is closer to civil law system but also classical criminal responsibility of an individual. Despite this fact, concurrent existence does not exclude any type of higher mentioned responsibilities. This article analyses also differences of rules applied to the responsibility of states and individuals. The most important conclusion for the present international law is connected with the needs of a separate convention in order to provide special regulations for the responsibility of states for the commission of breaches and grave breaches of humanitarian law of armed conflicts.